Scientific problem of modifying of primary crystals a β -phase of silumin castings. Solutions - E. I. Marukovich; V. Yu. Stetsenko (Литьë и металлургия, 2019)
It is shown that the phosphorum which is contained in a silumin melt in number of 0,01–0,04% exists in the dissolved form. For a solution of the problem of modifying of primary crystals of a β -phase in silumin castings it is necessary to accept a presumption that the oxygen adsorbed by a melt promotes decay and hinders the formation of crystallization centers of primary crystals of a β -phase. The role of phosphorum comes down to reduction of concentration of the adsorbed oxygen which works as the demodifier of primary microstructure of castings.